Detection of Foot and Mouth Disease Virus in Cattle in Lamongan and Surabaya, Indonesia Using RT-PCR Method - Dinana, Zayyin; Rantam, Fedik Abdul; Suwarno, Suwarno; Mustofa, Imam; Rahmahani, Jola; Kusnoto, Kusnoto (Jurnal Medik Veteriner, 2023)
Foot and mouth disease (FMD) virus was reported as an outbreak in Indonesia in April 2022 and belonged to serotype O/ME-SA/Ind-2001e is spread in the country. This study aimed to detect the causative agent based on clinical symptoms in cattle that have the vesicle in the mouth and hooves. A total of 25 samples were collected during August 2022 from Lamongan and Surabaya, Indonesia. FMD was identified in 58% (7/12) using reverse transcription polymerase chain reaction (RT-PCR), respectively. The samples were performed using universal primers with 328 bp length for primary diagnosis of FMD. These findings indicate that the spread of FMD viruses is highly contagious, so rapid and accurate diagnosis is needed as an effort to control and monitor FMD viruses.